Spatial and Temporal Distribution of Tuberculosis in the State of Mexico, Mexico - Adrian Zaragoza Bastida; Marivel Hernández Tellez; Lilia P. Bustamante Montes; Imelda Medina Torres; Jaime Nicolás Jaramillo Paniagua; Germán David Mendoza Martínez; Ninfa Ramírez Durán (The Scientific World Journal)
Tuberculosis (TB) is one of the oldest human diseases that still affects large population groups. According to the World Health Organization (WHO), there were approximately 9.4 million new cases worldwide in the year 2010. In Mexico, there were 18,848 new cases of TB of all clinical variants in 2010. The identification of clusters in space-time is of great interest in epidemiological studies. The objective of this research was to identify the spatial and temporal distribution of TB during the period 2006–2010 in the State of Mexico, using geographic information system (GIS) and SCAN statistics program. Nine significant clusters (𝑃<0.05) were identified using spatial and space-time analysis. The conclusion is that TB in the State of Mexico is not randomly distributed but is concentrated in areas close to Mexico City.